Comprehensive analysis of alfa defensin expression and prognosis in human colorectal cancer - Zhao, Xinliang; Lu, Mengnan; Liu, Zhigang; Zhang, Mingming; Yuan, Hongmei; Dan, Zhaoqiang; Wang, Daihua; Ma, Bingbing; Yang, Yanqi; Yang, Funing; Sun, Ruifang; Li, Lin; et al. (Frontiers in Oncology, 2023)
Colorectal cancer (CRC) is a serious threat to human health. Screening new biomarkers can provide basis for improving the prognosis and individualized treatment of CRC. Although some members of the defensin family were found increased in pancreatic cancer and CRC, their exact function and clinical significance remain unclear. In this study, the expression, correlation, mutation, and functional enrichment of several defensin family members in pancreatic cancer and CRC were analyzed using tumor public databases and verified in several patients. Results showed no significant correlation between the expression levels of DEFA1-4 and CRC. The expression levels of DEFA5 and DEFA6 significantly increased in CRC tissues compared with those in normal tissues. DEFA5 may be associated with better prognosis of CRC, while DEFA6 may be associated with poor prognosis. Immunohistochemistry (IHC) experiments showed that the expression of DEFA6 was significantly higher in adenoma than in normal mucosa and slightly higher in carcinoma than in normal mucosa. The Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis found that DEFAs were closely related to hsa05202: transcriptional misregulation in cancer and Hsa04015: Rap1 signaling pathway. DEFA5 may be a stable and good prognostic marker, and DEFA6 may be a poor prognostic marker in CRC of metastasis. Overall, DEFA5 and DEFA6 have a certain degree of sensitivity and specificity in predicting CRC.